Would Some Herbal Teas Play a Medicating Role for Certain Diseases? - Sattar, Tabinda (Current Nutrition & Food Science, 2021)
Herbal Teas prepared from leaves, roots, fruits, and flowers of different herbs contain many useful nutrients that may be a good replacement for medicating certain diseases. These herbal teas are very rich in poly-phenols, therefore are significant for their antioxidant, anti-inflammation, anticancer, anticardiovascular, antimicrobial, antihyperglycemic, and antiobesity properties. Medical chronic conditions, such as cardiovascular diseases, cancer, Alzheimer’s disease, Parkinson’s disease, constipation, diabetes, and bed wetting in children can be easily cured by the use of these herbal teas in regular and moderate amounts. This review focuses on the diverse constituents of herbal teas due to which these can be an attractive alternative towards promoting human health.
Keywords: roots herbal tea